The Island of Time: Yélî Dnye, the Language of Rossel Island - Levinson, Stephen C.; Majid, Asifa (Frontiers in Psychology, 2013)
This paper describes the linguistic description of time, the accompanying gestural system and the “mental time lines” found in the speakers of Yélî Dnye, an isolate language spoken offshore from Papua New Guinea. Like many indigenous languages, Yélî Dnye has no fixed anchoring of time and thus no calendrical time. Instead, time in Yélî Dnye linguistic description is primarily anchored to the time of speaking, with six diurnal tenses and special nominals for n days from coding time; this is supplemented with special constructions for overlapping events. Consequently there is relatively little cross-over or metaphor from space to time. The gesture system, on the other hand, uses pointing to sun position to indicate time of day and may make use of systematic time lines. Experimental evidence fails to show a single robust axis used for mapping time to space. This suggests that there may not be a strong, universal tendency for systematic space-time mappings.